2019
DOI: 10.1021/acs.jpcb.9b07405
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant-Free Microemulsion Based on CO2-Induced Ionic Liquids

Abstract: A novel surfactant-free microemulsion (SFME) based on CO2-induced ionic liquids (ILs) was prepared. Among them, dipropylamine (DPA) was directly reacted with CO2 to form the ILs that were composed of the ammonium salts and the ammonium carbamate salts, which was confirmed by 13C NMR, Fourier transform infrared, electrical conductivity, and pH. In addition, the purity of ILs was determined by 1H NMR. We used water as a polar phase, ILs as an amphi-solvent, and 1-dodecanol as a nonpolar phase to prepare SFME. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Due to the fact that acidic ILs are widely applied in the depolymerization of biomass with well activity and endowed with the feature of surfactivity in nature, the influence of different acidic ILs on lignin depolymerization in a typical microemulsion system (point d in Figure ) was investigated. From Figure B, it can be found that the catalytic performance of [C 3 H 6 SO 3 HMIm]­[HSO 4 ] (93.5 mg g –1 ) is better than those of [C 4 H 8 SO 3 HMIm]­[Cl] and [C 4 H 8 SO 3 HMIm]­[HSO 4 ] (55.6 and 68.1 mg g –1 respectively), and [HOOCMMIm]­[Cl] also shows a better catalytic activity than [HOOCEMIm]­[Cl] (60.0 and 51.7 mg g –1 , respectively).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the fact that acidic ILs are widely applied in the depolymerization of biomass with well activity and endowed with the feature of surfactivity in nature, the influence of different acidic ILs on lignin depolymerization in a typical microemulsion system (point d in Figure ) was investigated. From Figure B, it can be found that the catalytic performance of [C 3 H 6 SO 3 HMIm]­[HSO 4 ] (93.5 mg g –1 ) is better than those of [C 4 H 8 SO 3 HMIm]­[Cl] and [C 4 H 8 SO 3 HMIm]­[HSO 4 ] (55.6 and 68.1 mg g –1 respectively), and [HOOCMMIm]­[Cl] also shows a better catalytic activity than [HOOCEMIm]­[Cl] (60.0 and 51.7 mg g –1 , respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the fact that acidic ILs are widely applied in the depolymerization of biomass with well activity 37 and endowed with the feature of surfactivity in nature, 38 the influence of different acidic ILs on lignin depolymerization in a typical microemulsion system (point d in Figure 1) was investigated.…”
Section: Measurement and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to this, many researchers have introduced various stimulus responses into the emulsion (such as temperature response, magnetic response, , redox response, , light response, , CO 2 response, pH response, , etc.) in an attempt to make the stability and demulsification of the emulsion controllable.…”
Section: Introductionmentioning
confidence: 99%
“…At present, some methods have been proposed to improve the foaming behavior of PLA, such as chain extension, chain branching, and blending with other materials. Moreover, controlling crystallization kinetics of PLA during foaming has also been recognized as an effective way to improve its foaming behavior. Li et al reported a new supercritical fluid foaming process based on preisothermal cold crystallization for PLA, and foams with high expansion ratio were obtained .…”
Section: Introductionmentioning
confidence: 99%